(untitled) - Deutsch, Felix (New York, 1955)
Contents: The application of psychoanalytic concepts to resident training and the technique of the therapeutic interview; Depressive syndromes; Hysterical syndromes...
Keywords: Psychoanalysis,Phân tâm học